Cost Effective Antibiotics Versus Meropenem Against Extended Spectrum Beta Lactamase Producing Escherichia Coli from Urine - Waseem, Hafsa (International Journal of Pathology, 2022)
Introduction: urinary tract infections are one of the most common infectious diseases in the world. Escherichia coli is the most common cause of Urinary tract infection. Antibiotics are the routine therapy of urinary tract infection but due to misuse of them there is increasing resistance to them.Objective: To compare the in-vitro efficacy of cost effective antibiotics versus meropenem against Extended Spectrum Beta Lactamase producing Escherichia coli in urine.Methodology: Material and Methods: This Cross sectional descriptive study was conducted from 1st January 2018 to 31st May 2018 at the Department of Microbiology Army Medical College. Escherichia coli isolated from urine samples were first tested for the production of beta-lactamase. The susceptibility of Extended Spectrum Beta Lactamase producing Escherichia coli to fosfomycin, nitrofurantoin and meropenem was checked and compared.Results: A total of 133 extended spectrum beta lactamase producing Escherichia coli were isolated and tested. Out of these 99.25 % were susceptible to fosfomycin, 97% to nitrofurantoin and 95.5% to meropenem. Isolates were 3.75% more susceptible to fosfomycin and 1.75% more susceptible to nitrofurantoin than meropenem.Conclusion: Fosfomycin and nitrofurantoin was much more efficient against extended spectrum beta lactamase producing Escherichia coli as compared to meropenem. Easy to administer and being cost effective Fosfomycin and nitrofurantoin are very good options if to be used as first line therapy against extended spectrum beta lactamase producing Escherichia coli.